The concept of ethos in Ancient Greek music (Orfeu, 2017)
In this paper, the concept of ethos isconsidered as pertaining to the preceptsof Ancient Greece. Two works were takenas a starting point for these considerations: The Republic by Plato, and Politicsby Aristotle. By comparing these two philosophers, a discussion was made possiblewhich showed their conception of music’s impact on the placement of emotionsand on the character of citizens , as wellas the philosophers’ changing opinions inrelation to the role of music in society. Inthe context of this discussion, we conclude that a broader comprehension of ethosis central to the understanding of composers’ musical thought from Classical Antiquity, at least up to the Renaissance.
Keywords: ethos; Greek modes; music in Ancient Greece; church modes